Literature Review: Upaya Peningkatan Kesadaran Terhadap Kesiapsiagaan Bencana Kebakaran - Devina, Kayla; Putri Batubara, Aprilia; Hasibuan, Abdurrozzaq (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
Fire preparedness involves knowledge of how to avoid the causes of fire, how to respond quickly and effectively if a fire occurs, and measures to minimize the impact of a fire. Raising awareness about fire is an important step towards protecting lives, property and the environment, and ensuring better preparedness for fire disasters. The purpose of the study was to examine what efforts are important to increase awareness of preparedness in dealing with fire disasters. From the results of the journal review, some important efforts to increase awareness of preparedness in dealing with fire disasters are understanding the surrounding risks, understanding the early warning system, knowing the evacuation route, having the skills to know the situation quickly, reducing the impact of hazards through mitigation efforts, and participating in emergency response preparedness training.